2022
DOI: 10.3389/ffgc.2022.995537
|View full text |Cite
|
Sign up to set email alerts
|

Influence of topography, vegetation, weather, and climate on Big-cone Douglas-Fir fire refugia and high fire-induced mortality after two large mixed-severity wildfires

Abstract: Big-cone Douglas-Fir (Pseudotsuga macrocarpa, hereafter BCDF) is an endemic, fire-adapted conifer found throughout the mountains of southern California. Because recent large high intensity wildfires have resulted in loss of BCDF, understanding how environmental factors, such as topography, fuels, climate, and weather, impact BCDF survivorship is important for informing restoration and conservation efforts. Here, we used randomForest (RF) and accumulated local effects (ALE) plots to examine how environmental va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Hence restoration in those habitats makes little sense: conditions might appear to be more favorable initially due to somewhat more mesic conditions, but the ultimate fate of bigcone in chaparral vegetation is very poor due to the inevitability of stand-killing fires. By contrast, Parkinson et al (2022) found that association with Q. chrysolepis and with more open understory increased the likelihood of at least partial stand survival during large scale fires. Stands that suffered some mortality during fire but are in these refugia (open understory, or associations with oaks) could be selected as targets for postfire population enhancement through outplanting as done here.…”
Section: Synthesismentioning
confidence: 63%
See 2 more Smart Citations
“…Hence restoration in those habitats makes little sense: conditions might appear to be more favorable initially due to somewhat more mesic conditions, but the ultimate fate of bigcone in chaparral vegetation is very poor due to the inevitability of stand-killing fires. By contrast, Parkinson et al (2022) found that association with Q. chrysolepis and with more open understory increased the likelihood of at least partial stand survival during large scale fires. Stands that suffered some mortality during fire but are in these refugia (open understory, or associations with oaks) could be selected as targets for postfire population enhancement through outplanting as done here.…”
Section: Synthesismentioning
confidence: 63%
“…This study was initiated in response to the Zaca Fire that burned over 97,124 hectares in southern California from July to September 2007 including > 4,000 stands of bigcone Douglasfir (Parkinson et al, 2022). Selection of study sites was confined to the Zaca Fire perimeter.…”
Section: Site Selectionmentioning
confidence: 99%
See 1 more Smart Citation